Prevalence and contributors to anaemia among children aged 6 to 59 months in Kyangwali Refugee settlement, Western Uganda: a cross-sectional study - Christine Nakimera; Philip Bright Bwajojo; William Kaweesa; Joan Nampiima; Faith Chebet; Sharifah Namuwawu; Martin Bwemage; Moses Nuwabasa; Regina Ndagire; Allan Lugaajju; Joel Tumwebaze; Catherine Nassozi Lwanira (BMC Pediatrics)
Abstract Background Anaemia is a major cause of morbidity among children under five years in Uganda. However, its magnitude among refugee populations is marginally documented. In this study, the prevalence and contributors to anaemia among children 6 to 59 months in Kyangwali refugee settlement in Western Uganda was determined. Methods This was a cross-sectional study that was carried out among 415 mother- child dyads at Kwangwali refugee settlement. Anaemia was determined by measuring haemoglobin concentration using the HaemoCue method, while nutritional status was examined using standard World Health Organisation (WHO) nutritional indices. Data abstraction forms, pretested questionnaires and face to face interviews were used to collect patient data. Associations between the independent variables and anaemia were examined using modified Poisson regression with robust standard errors. In all statistical tests, a P- value of < 0.05 was considered as significant. Results The proportion of children with anaemia was 49.2% (95% CI: 44.4–53.9). Anaemia was 1.4 times (95% CI = 1.13–1.82; p = 0.003) more prevalent among wasted children than the normal children. The prevalence of anaemia was also higher among underweight children than those with normal weight (aPR = 1.37, 95% CI = 1.11–1.70; p = 0.004). Additionally, the prevalence of anaemia was higher among children of birth order of 6 or above (aPR = 2.00, 95% CI = 1.22–3.29; p = 0.006), while anaemia prevalence was lower among children whose mothers’ had attained secondary level of education (aPR = 0.19, CI = 0.04–0.98; p = 0.048) and those who fed on fish (aPR = 0.75, 95% CI = 0.57–0.99; p = 0.039) and meals prepared with oils and fats (aPR = 0.70, 95% CI = 0.51–0.97; p = 0.029). There was no significant relationship between anaemia occurrence and the household dietary diversity score. Conclusions About half of the study children were found to be anaemic. The most significant contributors to anaemia in the study population were malnutrition, maternal education, feeding practices and birth order. The study findings suggest need of screening of children for anaemia at all nutritional clinics, promotion of education, addressing barriers to sustainable food supply and accessibility of nutrient-dense foods, treating anaemia in children alongside other micronutrient deficiencies and addressing the nutritional needs of multiparous mothers in refugee communities.